PEMANFAATAN LIMBAH UNTUK KESEJAHTERAAN: PENGEMBANGAN PUPUK KOMPOS DAN ECO ENZYME DARI PRINSIP 4R DI KOTA LHOKSEUMAWE - Al Fahmi, muhammad lutfi; Alim, Muhammad Taqdirul; Maryana, Maryana; Rahman, Bobby; Syahnda, Aftri; Maulidin, Maulidin (Bestari: Jurnal Pengabdian Kepada Masyarakat, 2024)
The community service program "Waste Utilization for Welfare: Development of Compost Fertilizer and Eco Enzyme from the 4R Principle in Lhokseumawe City" aims to improve community welfare through the use of organic waste. The 4R principle (Reduce, Reuse, Recycle, and Replace) is the foundation of this program, which is to reduce the amount of waste and process waste into useful products such as compost and eco enzymes. The people of Lhokseumawe City are trained to make compost and eco enzyme fertilizers from household waste. Food scraps and foliage are converted into compost, which improves soil quality and increases local agricultural yields. On the other hand, eco enzymes, a liquid produced from the fermentation of organic waste, serve as a natural cleaner and liquid fertilizer that is economical and environmentally friendly. In addition, this activity provides knowledge to the community about the importance of good waste management to reduce the adverse impacts caused by waste. By applying the 4R principle, the community is expected to be able to manage daily waste more efficiently, resulting in products that are useful and have economic value. This training is also expected to encourage residents to make more money from waste treatment. By producing eco enzymes and compost, new business opportunities arise around. Overall, these efforts are not only concentrated on environmental issues, but also on improving the financial well-being of citizens. With effective waste management, it is hoped that the people of Lhokseumawe City will become more independent, environmentally conscious, and prosperous.